2010
DOI: 10.1521/aeap.2010.22.4.273
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Adaptation of a U.S. Evidence-Based Parenting Intervention for Rural Western Kenya: From Parents Matter! to Families Matter!

Abstract: Evidence-based interventions (EBIs) are critical for effective HIV prevention, but time and resources required to develop and evaluate new interventions are limited. Alternatively, existing EBIs can be adapted for new settings if core elements remain intact. We describe the process of adapting the Parents Matter! Program, an EBI originally developed for African American parents to promote effective parent-child communication about sexual risk reduction and parenting skills, for use in rural Kenya. A systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 19 publications
2
24
0
Order By: Relevance
“…Measures for the Kenya evaluation were chosen from the US evaluation. Previous formative work with the Asembo community around the context of sexuality education demonstrated that parents in Kenya and the US face similar barriers in communicating with their children about sexuality issues [35], providing support for the cultural relevancy of drawing from parenting constructs used in the US study for the Kenya evaluation. The measures were extensively pretested in Asembo; questions eliciting inconsistent responses were reviewed and revised by focus groups, program staff, and other community members for comprehension.…”
Section: Methodsmentioning
confidence: 84%
“…Measures for the Kenya evaluation were chosen from the US evaluation. Previous formative work with the Asembo community around the context of sexuality education demonstrated that parents in Kenya and the US face similar barriers in communicating with their children about sexuality issues [35], providing support for the cultural relevancy of drawing from parenting constructs used in the US study for the Kenya evaluation. The measures were extensively pretested in Asembo; questions eliciting inconsistent responses were reviewed and revised by focus groups, program staff, and other community members for comprehension.…”
Section: Methodsmentioning
confidence: 84%
“…8587 Similar strategies are now being adapted for and evaluated in parts of Sub-Saharan Africa. 88,89 Our findings, however, suggest that while interventions designed to increase parental behavioral control of youth, or to improve skills for managing conflict in youth-parent relationships, may have some effects on sexual behaviors, they may do little to protect adolescent females in Ghana from coerced sex.…”
Section: Discussionmentioning
confidence: 69%
“…We identified several models on the adaptation process developed across a range of different fields (e.g., psychology, education); for example, in relation to psychotherapy and evidencebased health interventions [4,[15][16][17][18][19][20][21][22][23]. We also identified frameworks evaluating online tools [24,25], implementation research models (e.g., Revised Ottawa Model of Research Use) [26], and technology and innovation models (e.g., Technology Acceptance Model) [27].…”
Section: Conceptual Modelmentioning
confidence: 99%